2020
DOI: 10.1088/1757-899x/805/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of silver nanoparticles biosynthesized from methanolic leaf extract of Blighia sapida

Abstract: Synthesis of nanoparticles by biological methods using microorganisms, enzymes or plant extracts has been suggested as possible ecofriendly alternative to chemical and physical methods which involve the use of harmful reducing agents. In the current study, silver nanoparticles (AgNPs) were synthesized by green approach from methanolic leaf extract of Blighia sapida. The synthesized AgNPs were characterized by UV-visible (UV-vis) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The strong antioxidant property exhibited by some nanomaterials is opening exciting potential to develop new regimens with enhanced and targeted actions. For instance, gold, silver and selenium nanoparticles have been shown to possess ability to reduce oxidative stress due to their efficient redox-active radical-scavenging properties [ 20 ]. Studies have shown that apple decreases the presence of ROS generated by hydrogen peroxide exposure in lymphocytes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strong antioxidant property exhibited by some nanomaterials is opening exciting potential to develop new regimens with enhanced and targeted actions. For instance, gold, silver and selenium nanoparticles have been shown to possess ability to reduce oxidative stress due to their efficient redox-active radical-scavenging properties [ 20 ]. Studies have shown that apple decreases the presence of ROS generated by hydrogen peroxide exposure in lymphocytes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant capacity of these nanoparticles could be attributed to the abundance of surface fabricated flavonoids and phenolics as capping agents [ 180 ]. In another study, Akintola et al [ 181 ] investigated the antioxidant effects of Ag NPs (synthesized using Blighia sapida leaves) using DPPH and reducing power assay. Ag NPs at different concentrations (50, 75, 100, 125, and 150 ÎŒ g/mL) scavenged DPPH by 58.10, 59.26, 62.33, 71.24, and 75.42%, respectively.…”
Section: Antioxidant Potential Of Phytoantioxidant Functionalized Nanoparticlesmentioning
confidence: 99%
“…The antioxidant activity of synthesized NiO NPs was determined by performing DPPH free radical scavenging assay as per the procedure described by Akintola et al (2020). To select concentrations of aqueous plant extract and the synthesized NPs solutions, an equal volume of methanolic DPPH (0.135 mm) solution was added and incubated at room temperature for 30 minutes.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%